2022
DOI: 10.21608/ejvs.2021.96527.1298
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Modified Buffy Coat Method As a Tool for Diagnosis of Bovine Hemoparasites

Abstract: M ODIFIED buffy coat method (BCM) using microhematocrit tubes and acridine orange (AO) staining permitsquick(~10 min/sample) and accurate diagnosis of commonbovine hemoparasites compared to the light microscopy(LM) of Giemsa stained smears.Babesia, Theileria,Anaplasma, Ehrlichia and Trypanosoma parasites were detected. It was easy to see Babesia merozoites, trypomastigotes and epimastigotes of Trypanosoma parasite. Similarly, fluorescent microscopy (FLM), offers a method for detecting low parasitemiathat are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Hansen et al (36) described acridine orange staining as a fluorochrome stain for the detection of deoxyribonucleic acid (DNA) in bovine babesiosis (37,38). Ravindran et al (39) described the acridine orange staining technique as an accurate, simple, and rapid screening of many blood samples. It was also reported that time for identification of first parasite was only 1/3 by acridine orange staining as compared to giemsa-stained smears (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al (36) described acridine orange staining as a fluorochrome stain for the detection of deoxyribonucleic acid (DNA) in bovine babesiosis (37,38). Ravindran et al (39) described the acridine orange staining technique as an accurate, simple, and rapid screening of many blood samples. It was also reported that time for identification of first parasite was only 1/3 by acridine orange staining as compared to giemsa-stained smears (40,41).…”
Section: Discussionmentioning
confidence: 99%